Um estudo da utilização de blog para disciplina de biologia - Melani, Aniceta da Conceição Antunes de Brito Alves (2017)
The use of technological resources is already a reality present in all the spheres of our society. The Information and Communication Digital Technologies (ICDT) have their use increased more and more, especially the Internet. When we talk about education, it is necessary to think and seek didactic proposals that relates with these new ways of teaching. This research aims to evaluate the interest and perception of the students to the use of a Blog as an easing tool in teaching and learning. This research targets classes of high school and we need to point out that this research is allied to a multidisciplinary project whose areas of knowledge are biology and arts. This research uses the qualitative method, focusing on the aspects of the daily life of our students. The methodological strategy is based on the application of an initial questionnaire, in addition to activities and a questionnaire of evaluation of the interest and use of the blog whose digital domain is the blog www.projetobioartes.com/wordpress, with the students of the first and second grades of the Colégio Estadual Círculo Operário, at Duque de Caxias, Rio de Janeiro. The results showed that from the use of the Blog, in biology classes, there was a satisfactory increase in both interest and perception of this discipline. Fact that is also demonstrated by the students in their positive comments at the end of the activities.